Culturing Rat Whole Ovary for UV Filter Benzophenone‐3 Treatment. Issue 1 (25th November 2019) - Santamaría, Clarisa Guillermina; Abud, Julián Elías; Luque, Enrique Hugo; Kass, Laura; Rodríguez, Horacio Adolfo
Abstract: We describe a detailed protocol to establish a newborn rat whole ovary culture, which enables the study of direct effects (independent of hypothalamic‐pituitary‐gonadal axis) of endocrine disrupting chemicals (EDCs), such as benzophenone‐3 (BP‐3). This method is useful to understand changes in follicle formation, primordial to primary transition, and expression of regulatory molecules linked to these processes and also provides an alternative to animal models. © 2019 by John Wiley & Sons, Inc. Basic Protocol 1 : Rat ovarian surgery Basic Protocol 2 : Whole organ/ovarian culture Basic Protocol 3 : RNA isolation and quantitative real‐time PCR Basic Protocol 4 : Histological processing and staining